Unique Design of Sports School Column: Innovation and Practical Application (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article provides rules for designing and calculating unique roof structures of sports schools. In addition, information is given on modern materials used in unique roof constructions of sports schools.